Autonomic regulation therapy to enhance myocardial function in heart failure patients: the ANTHEM‐HFpEF study. (28th December 2017) - DiCarlo, Lorenzo A.; Libbus, Imad; Kumar, H. Uday; Mittal, Sanjay; Premchand, Rajendra K.; Amurthur, Badri; KenKnight, Bruce H.; Ardell, Jeffrey L.; Anand, Inder S.
Abstract: Background: Approximately half of the patients presenting with new‐onset heart failure (HF) have HF with preserved left ventricular ejection fraction (HFpEF) and HF with mid‐range left ventricular ejection fraction (HFmrEF). These patients have neurohormonal activation like that of HF with reduced ejection fraction; however, beta‐blockers and angiotensin‐converting enzyme inhibitors have not been shown to improve their outcomes, and current treatment for these patients is symptom based and empiric. Sympathoinhibition using parasympathetic stimulation has been shown to improve central and peripheral aspects of the cardiac nervous system, reflex control, induce myocyte cardioprotection, and can lead to regression of left ventricular hypertrophy. Beneficial effects of autonomic regulation therapy (ART) using vagus nerve stimulation (VNS) have also been observed in several animal models of HFpEF, suggesting a potential role for ART in patients with this disease. Methods: The Autonomic Neural Regulation Therapy to Enhance Myocardial Function in Patients with Heart Failure and Preserved Ejection Fraction (ANTHEM‐HFpEF) study is designed to evaluate the feasibility, tolerability, and safety of ART using right cervical VNS in patients with chronic, stable HFpEF and HFmrEF. Patients with symptomatic HF and HFpEF or HFmrEF fulfilling the enrolment criteria will receive chronic ART with a subcutaneous VNS system attached to the right cervical vagus nerve. Safety parameters will be continuously monitored, and cardiac function and HF symptoms will be assessed every 3 months during a post‐titration follow‐up period of at least 12 months. Conclusions: The ANTHEM‐HFpEF study is likely to provide valuable information intended to expand our understanding of the potential role of ART in patients with chronic symptomatic HFpEF and HFmrEF.